Recent progress in inverted perovskite solar cells employing nickel oxide (NiOx) as a hole transport materials. (2021) - Kumar, Anjan; Singh, Sangeeta; Yadav, Anupam
Abstract: Perovskite solar cells (PSCs) have made phenomenal improvement in the power conversion efficiency from 3.8% in 2009 to 25.2% in 2020. Even though TiO2 continues to be the most used electron transport layer in PSCs, research in the field showed that n- type SnO2 when used on the transparent front electrode with conventional structure (n-i-p) has the highest device efficiency. However, their scope for further commercial application is limited due to the need for high temperature process and the comparatively higher J-V hysteresis in conventional (n-i-p) structure. Therefore, inverted device configuration (p-i-n) using NiOx as a hole transport material (HTM) has drawn considerable interest in the past several years. This is primarily due to their excellent chemical stability, smaller processing temperature for device fabrication, and good transmittance compared to organic HTMs. Deposition of NiOx hole transport material on the FTO/ITO substrate is an efficient way to improve the photo physics of manufacturing devices. It has shown impressive outcomes in inverted PSCs. Recent advances in the preparation of NiOx HTMs are detailed in this article. The impact of NiOx deposition on FTO/ITO substrate by different methods and their effect on electrical and optical properties was carefully studied. We also address the benefits and existing issues of using NiOx HTMs in PSCs and aim to foresee future success by incorporating them in high-efficiency inverted perovskite solar cell architecture.